Identification of a pathogenicity determinant of Plum pox virus in the sequence encoding the C-terminal region of protein P3+6K1 - Sáenz, Pilar; Cervera, Maria Teresa; Dallot, Silvie; Quiot, Laurence; Quiot, Jean-Bernard; Riechmann, José Luis; Garcı́a, Juan Antonio (Journal of General Virology, 2000)
A full-length genomic cDNA clone of a plum pox potyvirus (PPV) isolate belonging to the M strain (PPV-PS) has been cloned downstream from a bacteriophage T7 polymerase promoter and sequenced. Transcripts from the resulting plasmid, pGPPVPS, were infectious and, in herbaceous hosts, produced symptoms that differed from those of virus progeny of pGPPV, a full-length genomic cDNA clone of the D strain PPV-R. Viable PPV-R/-PS chimeric viruses were constructed by recombination of the cDNA clones in vitro. Analysis of plants infected with the different chimeras indicated that sequences encoding the most variable regions of the potyvirus genome, the P1 and capsid protein coding sequences, were not responsible for symptom differences between the two PPV isolates in herbaceous hosts. On the contrary, complex symptomatology determinants seem to be located in the central region of the PPV genome. The results indicate that a genomic fragment that encodes 173 aa from the C-terminal part of the P3+6K1 coding region is enough to confer, on a PPV-R background, a PS phenotype in Nicotiana clevelandii. This pathogenicity determinant also participates in symptom induction in Pisum sativum, although the region defining the PS phenotype in this host is probably restricted to 74 aa.